Escritas autobiográficas: por entre imaginários e memórias: a busca das confluências para tornar-me educadora - Krüger, Cristina Debli (2013)
Issues related to Education, imaginary and memory, which were discussed in this Master s thesis, have led to reflection on human (self)development. Writings about important elements that helped my development as an educator and the subject of this research were analyzed. This problematization emerged from the need to research on the reasons why a researcher became an educator. Thus, I tried to gather in my memory - an empirical source - the evidence, from childhood to these days, of potential (self)development aspects up to college education. The investigation aimed at problematizing the elements stored in memory that composed this way in the light of studies carried out by the Grupo de Estudos e pesquisas sobre Imaginário, Educação e Memória (GEPIEM / FaE), a study group in the Postgraduate Program in Education in the line Written Culture: languages and learning at the Universidade Federal de Pelotas, located in Pelotas, RS, Brazil. The following research sources were used to comprehend my life path: memories of my childhood and education processes, besides personal photographs. Based on them, I used literary writings to compose my reflections which were tools to create and understand my present life. The elements found in my development path, my father and two teachers I had in High School led me to identify the following cores: the use of symbolic strategies to educate, commit and like what I do. Therefore, I can infer that both imaginary and memory are fundamental to understand an autobiography, to think of and feel our education process. They play an important role towards selfknowledge.